2017
DOI: 10.1007/s10339-017-0851-4
|View full text |Cite
|
Sign up to set email alerts
|

Mouse-tracking evidence for parallel anticipatory option evaluation

Abstract: In fast-paced, dynamic tasks, the ability to anticipate the future outcome of a sequence of events is crucial to quickly selecting an appropriate course of action among multiple alternative options. There are two classes of theories that describe how anticipation occurs. Serial theories assume options are generated and evaluated one at a time, in order of quality, whereas parallel theories assume simultaneous generation and evaluation. The present research examined the option evaluation process during a task d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In the past 10 years, mouse tracking has become a popular method for studying the dynamics of cognitive processes in different domains, ranging from general decision making (Koop, 2013;Koop & Johnson, 2013;McKinstry, Dale, & Spivey, 2008) and social cognition (Freeman & Ambady, 2010;Freeman, Dale, & Farmer, 2011;Freeman & Johnson, 2016;Freeman, Pauker, & Sanchez, 2016) to phonetic competition (Cranford & Moss, 2017;Spivey, Grosjean, & Knoblich, 2005) and syntactic, semantic, and pragmatic processing (Dale & Duran, 2011;Farmer, Cargill, Hindy, Dale, & Spivey, 2007;Sauerland, Tamura, Koizumi, & Tomlinson, 2017;Tomlinson, Bailey, & Bott, 2013;andXiao &Yamauchi, 2014, 2017, among others).…”
Section: Introductionmentioning
confidence: 99%
“…In the past 10 years, mouse tracking has become a popular method for studying the dynamics of cognitive processes in different domains, ranging from general decision making (Koop, 2013;Koop & Johnson, 2013;McKinstry, Dale, & Spivey, 2008) and social cognition (Freeman & Ambady, 2010;Freeman, Dale, & Farmer, 2011;Freeman & Johnson, 2016;Freeman, Pauker, & Sanchez, 2016) to phonetic competition (Cranford & Moss, 2017;Spivey, Grosjean, & Knoblich, 2005) and syntactic, semantic, and pragmatic processing (Dale & Duran, 2011;Farmer, Cargill, Hindy, Dale, & Spivey, 2007;Sauerland, Tamura, Koizumi, & Tomlinson, 2017;Tomlinson, Bailey, & Bott, 2013;andXiao &Yamauchi, 2014, 2017, among others).…”
Section: Introductionmentioning
confidence: 99%
“…Cursor movement task We developed a bespoke online motor task (Fig. 2 ) adapted from previous literature that used cursor movement tasks to measure motor control (Cranford & Moss, 2018 ; Kimura & Nakano, 2019 ; Maraj et al, 2003 ). This continuous, closed-loop, precision motor task was chosen as it incorporates the speed accuracy trade off applicable to many areas of motor performance (such as sports; Beilock & Carr, 2001 ), a continuous element that is present in conscious control work in gait (Ellmers & Young, 2018 ), and offers enough complexity to potentially require multiple elements of verbalisable control.…”
Section: Methodsmentioning
confidence: 99%
“…Results showed that data closely corresponded to data collected using the same procedures in the lab. One method of collecting detailed data on movement execution that has been popular in the lab is mouse tracking (Cranford & Moss, 2018 ; Kieslich et al, 2019 ; Rheem et al, 2018 ). This process records coordinates of the participant’s cursor during task execution, a feature that is now available on the online data collection platform ‘Gorilla’ (Anwyl-Irvine et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that data closely corresponded to data collected using the same procedures in the lab. One method of collecting detailed data on movement execution that has been popular in the lab is mouse tracking (Cranford & Moss, 2018;Kieslich et al, 2018;Rheem et al, 2018). This process records coordinates of the participant's cursor during task execution, a feature that is now available on the online data collection platform 'Gorilla' (Anwyl-Irvine et al, 2020).…”
Section: Introductionmentioning
confidence: 99%